(untitled) (Journal of Philosophy Culture and Political Science, 2019)
Education appears as a fundamental category of culture. Education, as a way of entering the world of man in the national and world culture, has been instrumental in the development of its cultural identity. Culture is an important step in the educational process in the philosophical and educational ideas of Kant. In culture, according to Kant, it is a relevant abilities about how to improve your child all the knowledge, skills and abilities that are needed to achieve «any purpose». Kant speaks about the development of a culture of freedom. For Kant, in education play a role are three types of freedom. They should be the subject of culture. The purpose of education – to send the human race to perfection. The purpose of education is to Kant also contribute to a person appointed, to cultivate their human nature. One of the main objectives of education – acculturation. Keywords: еducation, philosophy of education, culture.